A prospective study of the correlation between infection of the uterine cervix and secondary bleeding after large loop excision of the transformation zone (LLETZ) : Prospektivna raziskava povezave med okužbo materničnega vratu in sekundarno krvavitvijo po eksciziji transformacijske cone z električno zanko (LLETZ) - Arko, Darja; Dovnik, Andraž; Fokter, Nina; Takač, Iztok (Acta Medico-Biotechnica, 2021)
Purpose: A prospective study was undertaken to evaluate the role of genital pathogens in postoperative bleeding necessitating secondary intervention after large loop excision of the transformation zone (LLETZ) of the uterine cervix.Methods: A total of 1419 patients with cervical intraepithelial neoplasia (CIN) who underwent LLETZ were included in the study. To determine the presence of genital pathogens, cervical swabs were collected before the procedure. Postoperatively, patients were followed up for bleeding necessitating secondary interventions.Results: Among 1419 patients, genital pathogens were present in 714 (50.3%) cases and absent in 705 (49.7%) cases. The most frequently isolated groups of microorganisms were group-B β-haemolytic streptococci, α-haemolytic streptococci, Enterococcus sp. and coliforms. Secondary procedures due to severe bleeding were required in 48 (6.8%) patients without and in 63 (8.8%) patients with genital pathogens, but this difference was not significant (chi-square test = 1.72; P>0.05).Conclusion: These data suggest that genital pathogens are very common in patients with CIN and are not an important cause of postoperative bleeding necessitating secondary intervention after LLETZ.
Keywords: cervical intraepithelial neoplasia; genital pathogens; LLETZ; bleeding; genital infection